2015
DOI: 10.2118/174093-pa
|View full text |Cite
|
Sign up to set email alerts
|

Upscaling Kinetics for Field-Scale In-Situ-Combustion Simulation

Abstract: Summary We demonstrate the effectiveness of a non-Arrhenius kinetic upscaling approach for in-situ-combustion processes, first discussed by Kovscek et al. (2013). Arrhenius reaction terms are replaced with equivalent source terms that are determined by a work flow integrating both laboratory experiments and high-fidelity numerical simulations. The new formulation alleviates both stiffness and grid dependencies of the traditional Arrhenius approach. Consequently, the computational efficiency and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 4 publications
0
20
0
Order By: Relevance
“…Kovscek et al [77][78][79] have developed a procedure for upscaling of reaction kinetics called Work-flow-based Upscaling-for Grid-Independence (WUGI). The procedure involves six steps: (1) selection of reaction model, (2) fitting of reaction model to kinetic cell and combustion tube experiments, (3) obtaining estimates for fuel-deposition fraction , (4) running highfidelity 1D simulations to obtain reference solutions for , (5) running two-dimensional (2D) simulations to assess the impact on of variations in heterogeneity and (6) assignment of the fuel amount in each grid block of a field-scale simulation using the local conditions and data assembled from sensitivity studies.…”
Section: Gas Mole Fractionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kovscek et al [77][78][79] have developed a procedure for upscaling of reaction kinetics called Work-flow-based Upscaling-for Grid-Independence (WUGI). The procedure involves six steps: (1) selection of reaction model, (2) fitting of reaction model to kinetic cell and combustion tube experiments, (3) obtaining estimates for fuel-deposition fraction , (4) running highfidelity 1D simulations to obtain reference solutions for , (5) running two-dimensional (2D) simulations to assess the impact on of variations in heterogeneity and (6) assignment of the fuel amount in each grid block of a field-scale simulation using the local conditions and data assembled from sensitivity studies.…”
Section: Gas Mole Fractionmentioning
confidence: 99%
“…The procedure involves six steps: (1) selection of reaction model, (2) fitting of reaction model to kinetic cell and combustion tube experiments, (3) obtaining estimates for fuel-deposition fraction χ , (4) running high-fidelity 1D simulations to obtain reference solutions for χ , (5) running two-dimensional (2D) simulations to assess the impact on χ of variations in heterogeneity and (6) assignment of the fuel amount in each grid block of a field-scale simulation using the local conditions and data assembled from sensitivity studies. 79 Figure 13 shows a comparison of 2D simulations using the conventional Arrhenius kinetics and the WUGI upscaling approach with grid blocks of different sizes.
Figure 13.In situ combustion upscaling in horizontal 2D 1/4 five spot case (from Zhu et al.
…”
Section: Challenges and Opportunitiesmentioning
confidence: 99%
“…The use of dynamic gridding still has not fully solved the demanding grid size problem in field-scale ISC simulations. In recent years, a novel reaction upscaling method has been proposed in order to minimize the grid size effect in fieldscale ISC simulations [14,15]. Both the temporal and spatial scales of kinetics and advection are very different in the ISC process.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we choose D block as the case of study to show the simulation of the ISC process from laboratory to field scale. Based on the methodology proposed in our previ-ous work [4,14,15], we present a comprehensive case study on the simulation of heavy oil in-situ combustion from laboratory experiment to field-scale simulation. It includes kinetic cell (RTO) and combustion tube laboratory experiments, establishing kinetic reaction model, history match of experiments, and finally field-scale simulation using the proposed upscaled reaction model.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, given that Petrobank had experienced excessive sand production that might have also hindered and thus limited the flow rates of the mobilised upgraded oil into the HP well, lack of understanding of physicochemical and fluid dynamics inside the reservoir could very well be to blame for the failure to establish the well-structured combustion front and to achieve high oil production rates. In fact, multiple studies (Ado 2020a, b;Kovscek et al 2013;Nissen et al 2015) have shown that laboratory-scale validated numerical models are incapable of predicting the physicochemical transport processes in field-scale reservoirs. However, what these studies did not observe and show are the differences especially in terms of reservoir flow dynamics between the laboratoryscale and the field-scale models.…”
Section: Introductionmentioning
confidence: 99%